Malignant catatonia due to anti-NMDA-receptor encephalitis in a 17-year-old girl: case report - Vidailhet Marie; Amoura Zahir; Didelot Adrien; Bonnot Olivier; Maksud Philippe; Montefiore Delphine; Costedoat-Chalumeau Nathalie; Marra Donata; Barbeau Martine; An-Gourfinkel Isabelle; Ronen Karine; Consoli Angèle; et al. (BMC, 2011)
Abstract Anti-NMDA-Receptor encephalitis is a severe form of encephalitis that was recently identified in the context of acute neuropsychiatric presentation. Here, we describe the case of a 17-year-old girl referred for an acute mania with psychotic features and a clinical picture deteriorated to a catatonic state. Positive diagnosis of anti-NMDA-receptor encephalitis suggested specific treatment. She improved after plasma exchange and immunosuppressive therapy. Post-cognitive sequelae (memory impairment) disappeared within 2-year follow-up and intensive cognitive rehabilitation.